Creation of transgenic mice susceptible to coronaviruses: a platform for studying viral pathogenesis and testing vaccines - N. R. Battulin; O. L. Serov (Вавиловский журнал генетики и селекции)
Over the past 20 years, coronaviruses have caused three epidemics: SARS-CoV, MERS-CoV, and SARS-CoV2, with the first two having a very high lethality of about 10 and 26 %, respectively. The last outbreak of coronavirus infection caused by SARS-CoV2 in 2019 in China has swept the entire planet and is still spreading. The source of these viruses in humans are animals: bats, Himalayan civets, and camels. The genomes of MERS-CoV, SARS-CoV and SARS-CoV2 are highly similar. It has been established that coronavirus infection (SARS-CoV and SARS-CoV2) occurs through the viral protein S interaction with the lung epithelium – angiotensin-converting enzyme receptor 2 (ACE2) – due to which the virus enters the cells. The most attractive model for studying the development of these diseases is a laboratory mouse, which, however, is resistant to coronavirus infection. The resistance is explained by the difference in the amino acid composition of mouse Ace2 and human ACE2 proteins. Therefore, to create mice susceptible to SARS-CoV and SARS-CoV2 coronaviruses, the human ACE2 gene is transferred into their genome. The exogenous DNA of the constructs is inserted into the recipient genome randomly and with a varying number of copies. Based on this technology, lines of transgenic mice susceptible to intranasal coronavirus infection have been created. In addition, the use of the technology of targeted genome modification using CRISPR/Cas9 made it possible to create lines of transgenic animals with the insertion of the human ACE2 gene under the control of the endogenous murine Ace2 gene promoter. This “humanization” of the Ace2 gene makes it possible to obtain animals susceptible to infection with coronaviruses. Thus, transgenic animals that simulate coronavirus infections and are potential platforms for testing vaccines have now been created.